Factors Affecting the Adoption Intensity of Farm Machinery Among Wheat Farmers in Rupandehi District, Nepal - Pandey, Jamuna; Mishra, Binayak Prakash (Journal of the Institute of Agriculture and Animal Science, 2025)
An investigation was done in 2025 to identify the factors affecting the adoption intensity of farm machinery among wheat farmers in Rupandehi district, Nepal. Using a random sampling technique, 120 farm households within the wheat zone area of the Prime Minister Agriculture Modernization Project (PMAMP) were selected. Primary data was collected through household surveys using a semi-structured interview schedule. In addition, Focus Group Discussions (FGDs) and Key Informant Interviews (KIIs) were also conducted with selected individuals. Descriptive statistics and an ordered Probit model were employed to analyze the data using STATA 17. The results revealed that both institutional and resource-related factors significantly influenced the adoption intensity of farm machinery. Specifically, membership in agricultural cooperatives, farm size, and access to government subsidies through PMAMP positively and significantly affected adoption intensity. These findings suggest that strengthening cooperative institutions, promoting land consolidation or collective use models such as group farming, and maintaining targeted subsidy programs are vital for accelerating the adoption of farm machinery in wheat production. Furthermore, mechanization policy should adopt a holistic approach that integrates institutional support, land-use planning, and financial incentives to facilitate sustainable agricultural mechanization.